2021
DOI: 10.1111/acer.14545
|View full text |Cite
|
Sign up to set email alerts
|

You Didn’t Drink During Pregnancy, Did You?

Abstract: Background Accurate characterization of prenatal alcohol exposure (PAE) is challenging due to inconsistent use of screening questionnaires in routine prenatal care and substantial underreporting due to stigma associated with alcohol use in pregnancy. The aim of this study was to identify self‐report tools that are efficient in accurately characterizing PAE. Methods Participants meeting eligibility criteria for mild‐to‐moderate PAE were recruited into the University of New Mexico Ethanol, Neurodevelopment, Infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…The mean number of binge episodes during the month around LMP was 3.71 ± 5.75. During pregnancy, the average AAD reported on the TLFB calendars was estimated at 0.001 ± 0.01 (<1 drink/month); however, 89.6% of participants reported at least one binge drinking episode (≥4 drinks/occasion) using a combination of TLFB and targeted questions about episodic binge drinking (e.g., maximum number of drinks consumed in a 24-h period since LMP) [ 51 ]. Cumulatively across the periconceptional period and pregnancy, mean AAD in the PAE group was 0.15 ± 0.28 (equivalent to approximately 2 drinks/week).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean number of binge episodes during the month around LMP was 3.71 ± 5.75. During pregnancy, the average AAD reported on the TLFB calendars was estimated at 0.001 ± 0.01 (<1 drink/month); however, 89.6% of participants reported at least one binge drinking episode (≥4 drinks/occasion) using a combination of TLFB and targeted questions about episodic binge drinking (e.g., maximum number of drinks consumed in a 24-h period since LMP) [ 51 ]. Cumulatively across the periconceptional period and pregnancy, mean AAD in the PAE group was 0.15 ± 0.28 (equivalent to approximately 2 drinks/week).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, average estimates from the TLBF calendars were less than 1 drink per month, which has traditionally been considered negligible. However, we have previously demonstrated that pregnant persons might disclose alcohol use during pregnancy more openly if they are asked targeted questions, such as the maximum number of drinks consumed in a 24 h period since LMP and the number of drinks last time they consumed alcohol (with the date of last drink being compared to LMP) [ 51 ]. In fact, using such targeted questions and data from TLFB interviews, almost 90% of participants in the PAE group reported at least one binge drinking episode since LMP.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that self-reported alcohol and substance use was validated by a panel of biomarkers. The combined use of repeated, prospective TLFB interviews, targeted questions about binge drinking episodes, and a broad panel of ethanol biomarkers is the most comprehensive approach to characterize PAE ( Bakhireva and Savage, 2011 ; Bakhireva et al, 2021 ). Further, we have previously reported high concordance between disclosure of less stigmatized substances, such as cannabis, and urine drug tests ( Garg et al, 2016 ; Page et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This could be problematic because as evidenced in the analyses, individual ACEs have unequal weight of effect on later health outcomes and the trauma of losing a parent during childhood may not be the same as the impact of parental divorce or separation. Fourth, data on sensitive topics such as ACEs or prenatal substance use may be underreported due to associated stigma, fear of repercussions, and limited measures to elicit honest responses (Bakhireva, Leeman, Roberts, Rodriguez, & Jacobson, 2021 ). Fifth, although maternal sociodemographic characteristics during pregnancy were included as covariates in all the analyses, (epi)genetics, which may be important confounding factors in many of the relationships explored, were not accounted for.…”
Section: Strengths and Limitationsmentioning
confidence: 99%